2016
DOI: 10.1001/jamaoto.2015.3595
|View full text |Cite
|
Sign up to set email alerts
|

Association of Compliance With Process-Related Quality Metrics and Improved Survival in Oral Cavity Squamous Cell Carcinoma

Abstract: IMPORTANCE Quality metrics for patients with head and neck cancer are available, but it is unknown whether compliance with these metrics is associated with improved patient survival. OBJECTIVE To identify whether compliance with various process-related quality metrics is associated with improved survival in patients with oral cavity squamous cell carcinoma who receive definitive surgery with or without adjuvant therapy. DESIGN, SETTING, AND PARTICIPANTS A retrospective cohort study was conducted at a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
3
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 26 publications
(38 reference statements)
5
82
3
1
Order By: Relevance
“…In other studies, 13,21 multidisciplinary tumor board evaluation for patients with locally advanced head and neck cancer was associated with favorable oncologic outcomes, 21 and congruence between multidisciplinary treatment planning conference recommendations and actual treatment provided conferred a survival benefit in a heterogeneous cohort of patients with head and neck cancer. 13 A prior study 12 that evaluated quality metrics for surgically treated oral cavity SCC found no association between multidisciplinary evaluation and survival. Oral cavity SCC is managed almost exclusively with up-front surgery, suggesting that multidisciplinary evaluation may be more beneficial for planning optimal therapy in the setting of 2 or more alternative treatment options, particularly when decision making is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In other studies, 13,21 multidisciplinary tumor board evaluation for patients with locally advanced head and neck cancer was associated with favorable oncologic outcomes, 21 and congruence between multidisciplinary treatment planning conference recommendations and actual treatment provided conferred a survival benefit in a heterogeneous cohort of patients with head and neck cancer. 13 A prior study 12 that evaluated quality metrics for surgically treated oral cavity SCC found no association between multidisciplinary evaluation and survival. Oral cavity SCC is managed almost exclusively with up-front surgery, suggesting that multidisciplinary evaluation may be more beneficial for planning optimal therapy in the setting of 2 or more alternative treatment options, particularly when decision making is complex and multifactorial.…”
Section: Discussionmentioning
confidence: 96%
“…16 Additional potential quality metrics with face validity were developed in a multidisciplinary fashion at our institution as previously described. 12 …”
Section: Methodsmentioning
confidence: 99%
“…Despite the NCCN’s endorsement of the preferred time to initiation of PORT for patients with HNSCC, the evidence underlying the recommendation is conflicted with regards to its effect on locoregional recurrence and survival 13 , with some finding benefit 1421 and others finding no influence 10,11,2226 . Many of these studies have been limited by retrospective single institution study design and small patient numbers 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown inconsistent effects on locoregional recurrence and survival, with some finding benefit 1421 and others no influence 10,11,2226 . Most of the studies finding benefit to earlier initiation of adjuvant therapy were conducted over 15 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Discrepancies between guideline-directed care and delivered care have been described across the spectrum of pretreatment evaluation, treatment, and posttreatment surveillance for patients with oral cavity cancer 13 and laryngeal cancer 14,15 and in the receipt of adjuvant therapy for patients who have head and neck cancer with high-risk features. Discrepancies between guideline-directed care and delivered care have been described across the spectrum of pretreatment evaluation, treatment, and posttreatment surveillance for patients with oral cavity cancer 13 and laryngeal cancer 14,15 and in the receipt of adjuvant therapy for patients who have head and neck cancer with high-risk features.…”
Section: Frequency Of Care That Does Not Adhere To Nccn Guidelinesmentioning
confidence: 99%